Development and Evaluation of Gastroretentive Bioadhesive Tablet of Atenolol Using a Naturally Occurring Biodegradable Polymer - Soman, Soji; Basheer, Aysha Padinhar; Mol, Geethu; Muneer, Luthfa Ahamed; Rahiman, Mariyammath Rafeeqa Khazi Abdul; Fernandes, Gasper; Mutalik, Srinivas (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim Using atenolol as a model active pharmaceutical and galactomannan from the seeds of Trigonella foenumgraecum as a mucoadhesive polymer, an effort was made to develop a gastroretentive bioadhesive floating delivery system to improve the residence time in the stomach. Materials and Methods Different formulations were made with Hydroxypropyl Methyl Cellulose (HPMC) and galactomannan. Galactomannan was chosen because of its exceptional swelling properties in aqueous environments. In this investigation, citric acid and sodium bicarbonate were utilized as gas-producing components. Pre- and postcompression evaluations were performed on the manufactured tablets. The floating properties as well as the atenolol release pattern were investigated. Results The extracted polymer was characterized using various techniques and found to be similar to literature. The results from GC analysis showed a residual acetone content of 0.127 ppm, indicating that the extracted polymer is safer to use in the formulation of gastroretentive tablets. The physicochemical properties of the manufactured tablets were satisfactory in terms of swelling index, release characteristics, and buoyancy pattern. All of the manufactured batches had adequate in vitro buoyancy. The gastroretentive tablet exhibited axial and radial swelling throughout the in vitro buoyancy test. According to the testing, the formulation remained buoyant for approximately 8 to 12 hr. Conclusion According to the results of the evaluation, the manufactured tablet has a pleasing look, is heat stable, and is therapeutically efficient. F3 was determined to be the optimal formulation based on the data collected.
Keywords: Atenolol; Galactomannan; Gastroretentive floating bioadhesive tablets; HPMC; Natural polymer